Growth in the first two years of uninfected children born to HIV-1 seropositive mothers. Issue 2 (1st August 1998) - Agostoni, C; Zuccotti, G V; Giovannini, M; Decarlis, S; Giannì, M L; Piacentini, E; D'Auria, E; Riva, E
Abstract : OBJECTIVE: To assess the growth curves of uninfected infants born to type 1 human immunodeficiency virus (HIV-1) seropositive mothers by means of standardised anthropometric indices. METHODS: The z scores (National Center for Health Statistics–World Health Organisation data) of weight for age, length for age, and weight for length of 92 uninfected full term infants born to HIV positive mothers were compared with those of 65 bottle fed full term infants born to healthy mothers at 0, 1, 2, 3, 4, 6, 9, 12, 18, and (in a subgroup) 24 months of age. Confounders were also recorded. RESULTS: The study population had a lower length for age z score at birth (95% confidence intervals (CI): 0.02, −0.58) and higher weight for length z scores at 1 (95% CI: 0.21, 0.63), 2 (95% CI: 0.25, 0.66), and 3 (95% CI: 0.0, 0.48) months compared with the reference group. After a temporary recovery, the length for age z score difference increased progressively from the 4th month onwards and was significant at 18 (95% CI: −0.31, −1.05) and 24 (95% CI: −0.02, −0.91) months. The difference between the length for age z scores at birth was associated with maternal covariates, but the between group difference at 18 months was apparent even after adjustment for covariates. CONCLUSION: Uninfected infants born to HIV positive mothers have a rapid weight gain immediately after birth. A decrease in length progression during the second year might be a result of the social risk connected with the family environment and an unfavourable programming related to the maternal HIV status.